1981
DOI: 10.1212/wnl.31.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal glycogen storage disease with normal acid maltase

Abstract: Two unrelated 16-year-old boys had mental retardation, cardiomegaly, and proximal myopathy. One also had hepatomegaly. Histochemistry and electronmicroscopy of muscle biopsies showed lysosomal glycogen storage resembling acid maltase deficiency. Biochemical studies of skeletal muscle showed increased content of glycogen of normal structure; acid alpha-glucosidase activity in both urine and muscle was normal. Other enzymes of glycogen metabolism were also normal. The cause of this apparently generalized glycoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
209
1
18

Year Published

1982
1982
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(232 citation statements)
references
References 0 publications
4
209
1
18
Order By: Relevance
“…A dystrophin gene (DMD) mutation was found in the larger family; a DMD mutation was not detected in XLCM-2, which consisted of a mildly affected mother who had three sons manifesting a dilated cardiomyopathy phenotype (Ortiz-Lopez et al 1997) Mutations in another X-linked gene, lysosome-associated membrane protein-2 (LAMP-2), are an increasingly recognized cause of X-linked cardiomyopathy. Also known as Danon disease, the original phenotype description included a triad of non-obstructive hypertrophic cardiomyopathy (HCM), skeletal myopathy, and mental retardation in males (Danon et al 1981). Histological skeletal muscle findings mimic those of Pompe disease, and the cardiomyopathy is most commonly described as hypertrophic in males.…”
Section: Introductionmentioning
confidence: 99%
“…A dystrophin gene (DMD) mutation was found in the larger family; a DMD mutation was not detected in XLCM-2, which consisted of a mildly affected mother who had three sons manifesting a dilated cardiomyopathy phenotype (Ortiz-Lopez et al 1997) Mutations in another X-linked gene, lysosome-associated membrane protein-2 (LAMP-2), are an increasingly recognized cause of X-linked cardiomyopathy. Also known as Danon disease, the original phenotype description included a triad of non-obstructive hypertrophic cardiomyopathy (HCM), skeletal myopathy, and mental retardation in males (Danon et al 1981). Histological skeletal muscle findings mimic those of Pompe disease, and the cardiomyopathy is most commonly described as hypertrophic in males.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in some patients with adult form neutral a-glucosidase activity was dificient in the heart or muscle (DiMauro et al 1978;Shanske et al 1984). In addition, it has been reported that the coexistence of infantile and adult forms in the same family (Busch et al 1979;Loonen et al 1981) and lysosomal glycogen storage disease (glycogenosis type II) without acid aglucosidase deficiency (Danon et al 1981;Riggs et al 1983). At the present time, the correlation between variability of clinical phenotypes and biochemical abnormalities is still obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Danon disease (OMIM #300257) is a rare X-linked disorder originally described as a Pompe disease phenocopy with normal acid maltase activity (Danon et al 1981). The cardinal features of this condition are hypertrophic cardiomyopathy, preexcitation and tachyarrhythmias, and skeletal myopathy, with some affected persons manifesting intellectual disability and/or pigmentary retinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…The disease process is characterized pathologically by progressive interstitial fibrosis, muscle fiber hypertrophy, periodic-acid-Schiff-positive sarcoplasmic vacuolation, and myofibrillar disarray (Murakami et al 1995;Sugie et al 2005). Affected tissues accumulate abnormal autophagosomes containing bulk cytoplasmic debris and glycogen, bounded by a membrane expressing peculiar sarcolemma-like features (e.g., dystrophin and sarcoglycan staining) (Danon et al 1981;Sugie et al 2005;Tanaka et al 2000;González-Polo et al 2005).…”
Section: Introductionmentioning
confidence: 99%